Probing Oxygen Defects in Na0.5Bi0.5TiO3 Ferroelectric by Micro‐Raman Spectroscopy (Phys. Status Solidi B 7/2018) - Selvamani, Rachna; Singh, Gurvinderjit; Sathe, Vasant; Tiwari, Vidya Sagar (physica status solidi (b), 2018)
Conventional sintering of sodium bismuth titanate Na0.5Bi0.5TiO3 (NBT), a well‐known lead‐free ferroelectric material, results in the formation of oxygen vacancies, which leads to increased electrical conductivity, making technical application difficult. Various techniques have been used for oxygen defect analysis, among them impedance spectroscopy, but the highly insulating nature of ferrroelectric oxides requires high temperature for these investigations. Raman spectroscopy, recently used to study the defect‐related vibration modes in graphene and other oxide materials, provides useful information even at room temperature. Gurvinderjit Singh and co‐workers (article no. 1800002) use the micro‐Raman scattering technique to observe the oxygen defect‐related vibration mode in NBT. The concentration of oxygen defects is changed by making a solid solution of NBT with BiCrO3. The cover figure represents the obtained micro Raman spectra of (1–x)NBT–xBiCrO3 for different ‘x’ values, i.e. different amount of BiCrO3. An anomalous increase in the band intensity between 700 to 900 cm−1 (i.e. shaded region) is due to the presence of oxygen defects. This increase in band intensity signifies the increase in oxygen defect concentration with increase in BiCrO3 content.